Water Splitting: Electronically Double‐Layered Metal Boride Hollow Nanoprism as an Excellent and Robust Water Oxidation Electrocatalysts (Adv. Energy Mater. 13/2019). Issue 13 (4th April 2019) - Han, HyukSu; Hong, Yu‐Rim; Woo, Jungwook; Mhin, Sungwook; Kim, Kang Min; Kwon, Jiseok; Choi, Heechae; Chung, Yong‐Chae; Song, Taeseup
Abstract : In article number1803799, Heechae Choi, Yong‐Chae Chung, Taeseup Song and co‐workers report that an electronically double‐layered structure in quaternary metal‐metalloid hollow nanoprism can substantially enhance water oxidation activity as well as the stability of metalmetalloids in alkaline media. Double‐layered vanadium enhances charge transfer at the surface as well as the carrier concentration at the Fermi level. Furthermore, it can also prevent the surrounding metal atoms from leaching out and, as a result, substantially improves electrocatalytic stability of quaternary metal‐metalloid compounds for water oxidation in an alkaline medium.